Information Needs in Service Systems - A Framework for Integrating Service and Manufacturing Business Processes - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Oliver, Müller (Proceedings of the 44th Annual Hawaii International Conference on System Sciences, 2011)
Customer solutions comprise services and physical goods as integrated value propositions. Understanding the customers' point of view on value creation and integrating customers as co-creators of value into service processes are important research fields in Service Science Management and Engineering. At the same time, a lack of investigation of the providers' points of view on offering and fulfilling integrated value propositions can be ascertained. To compensate for this deficit, our paper investigates four different integrated value propositions in the B2B-market to study how an integration of service and manufacturing processes can be accomplished by sharing information in service systems. Based on in- depth business process analyses, information needs arising from the integration of service processes and manufacturing processes are identified and systematized in a conceptual framework. From a service research point of view, this framework provides a fundament to build on in consecutive qualitative and empirical investigations as well as for designing IT artifacts.
Keywords: B2B market; Business process analyses; Information needs; Manufacturing business processes; Service Management; Service systems